A Review of Key Performance Indicators for Building Flexibility Quantification to Support the Clean Energy Transition - Girolama Airò Farulla; Giovanni Tumminia; Francesco Sergi; Davide Aloisio; Maurizio Cellura; Vincenzo Antonucci; Marco Ferraro (Energies, 2021)
The transition to a sustainable society and a carbon-neutral economy by 2050 requires extensive deployment of renewable energy sources that, due to the aleatority and non-programmability of most of them, may seriously affect the stability of existing power grids. In this context, buildings are increasingly being seen as a potential source of energy flexibility for the power grid. In literature, key performance indicators, allowing different aspects of the load management, are used to investigate buildings’ energy flexibility. The paper reviews existing indicators developed in the context of theoretical, experimental and numerical studies on flexible buildings, outlining the current status and the potential future perspective. Moreover, the paper briefly reviews the range of grid services that flexible buildings can provide to support the reliability of the electric power system which is potentially challenged by the increasing interconnection of distributed variable renewable generation.